The Old Testament prophets - Heaton, E. W. 1920-1996 (A Pelican book, 1958)
This book has been written in the conviction that the prophetic tradition is the most vital part of Christianity's debt to Judaism and an indispensable witness to the nature of religious truth. Guides the reader through the prophetic writings, sketching the historical situation in which their message was delivered and explaining the manner of their composition. After considering the unparalleled phenomenon of Old Testament prophecy and the individual contributions of its greatest representatives, the author discusses the bearing of their outlook on a problem which is at present again the subject of active debate -- the relationship between religion and morality. The final chapter traces the stages by which the faith of the prophets was shaped to become the preparation for the coming of Christ.